Handbook of Biopolymers and Biodegradable Plastics : Properties, Processing, and Applications - Ebnesajjad, Sina (PDL handbook series., 2013)
Biopolymers and Biodegradable Plastics are a hot issue across the Plastics industry, and for many of the industry sectors that use plastic, from packaging to medical devices and from the construction indusry to the automotive sector. This book brings together a number of key biopolymer and biodegradable plastics topics in one place for a broad audience of engineers and scientists, especially those designing with biopolymers and biodegradable plastics, or evaluating the options for switching from traditional plastics to biopolymers. Topics covered include preparation, fabrication, applications and recycling (including biodegradability and compostability). Applications in key areas such as films, coatings controlled release and tissue engineering are discussed. Dr Ebnesajjad provides readers with an in-depth reference for the plastics industry - material suppliers and processors, bio-polymer producers, bio-polymer processors and fabricators - and for industry sectors utilizing biopolymers - automotive, packaging, construction, wind turbine manufacturers, film manufacturers, adhesive and coating industries, medical device manufacturers, biomedical engineers, and the recycling industry. Essential information and practical guidance for engineers and scientists working with bioplastics, or evaluating a migration to bioplastics. Includes key published material on biopolymers, updated specifically for this Handbook, and new material including coverage of PLA and Tissue Engineering Scaffolds. Coverage of materials and applications together in one handbook enables engineers and scientists to make informed design decisions.